2017
DOI: 10.3390/f8120463
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of Global Change on Mediterranean Forests and Their Services

Abstract: The increase in aridity, mainly by decreases in precipitation but also by higher temperatures, is likely the main threat to the diversity and survival of Mediterranean forests. Changes in land use, including the abandonment of extensive crop activities, mainly in mountains and remote areas, and the increases in human settlements and demand for more resources with the resulting fragmentation of the landscape, hinder the establishment of appropriate management tools to protect Mediterranean forests and their pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
72
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 120 publications
(82 citation statements)
references
References 260 publications
1
72
0
2
Order By: Relevance
“…For instance, a long‐term study carried out in the Ram Mountain suggested that in poor years, bighorn males reduce their investment in horn growth and increase the relative allocation of resources to summer mass gain, probably trading off long‐term reproductive success for short‐term survival (Douhard et al 2017). Even though habitat effects were demonstrated at a limited scale, our findings can be extended to the landscape scale because the forest encroachment at the expense of shrubs and grass‐rich open areas occurred at high rates throughout Mediterranean ecosystems (Peñuelas et al 2017).…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…For instance, a long‐term study carried out in the Ram Mountain suggested that in poor years, bighorn males reduce their investment in horn growth and increase the relative allocation of resources to summer mass gain, probably trading off long‐term reproductive success for short‐term survival (Douhard et al 2017). Even though habitat effects were demonstrated at a limited scale, our findings can be extended to the landscape scale because the forest encroachment at the expense of shrubs and grass‐rich open areas occurred at high rates throughout Mediterranean ecosystems (Peñuelas et al 2017).…”
Section: Discussionmentioning
confidence: 85%
“…The western Mediterranean basin has experienced increasing aridity since the 1970s (Kelley et al 2012). Rising temperatures together with decreasing precipitation and agricultural land abandonment have affected the landscape configuration by promoting the encroachment of grasslands by drought‐resistant woody shrubs (Peñuelas et al 2017). The loss of grass‐rich open areas caused a decrease in the resource quantity and quality for grazers and mixed‐feeders, such as the Iberian ibex (Martínez 1994, 2000).…”
Section: Hypothesis Rationale and Predictions On The Variables Thatmentioning
confidence: 99%
“…The new shape of this landscape has direct biological and cultural consequences and also has consequences for the potential impact of natural hazards such as forest fires [19,22,47,48]. The loss of landscape heterogeneity and diversity implies the loss of ecological functionality [8,9,11].…”
Section: Discussionmentioning
confidence: 99%
“…Molecular marker studies have not yet been published for the genus Quercus in the Apulian region. However, the evaluation of genetic variation can be of great importance for the conservation and management of forest ecosystems, especially in areas particularly vulnerable to climatic change (Peñuelas et al 2017) and in forests whose original extent has been significantly reduced. This is the case of the oak forests of the Apulia region.…”
Section: Introductionmentioning
confidence: 99%